2014
DOI: 10.3390/rs61212275
|View full text |Cite
|
Sign up to set email alerts
|

Landsat-8 Operational Land Imager Radiometric Calibration and Stability

Abstract: Abstract:The Landsat-8 Operational Land Imager (OLI) was radiometrically calibrated prior to launch in terms of spectral radiance, using an integrating sphere source traceable to National Institute of Standards and Technology (NIST) standards of spectral irradiance. It was calibrated on-orbit in terms of reflectance using diffusers characterized prior to launch using NIST traceable standards. The radiance calibration was performed with an uncertainty of ~3%; the reflectance calibration to an uncertainty of ~2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
154
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 15 publications
3
154
0
2
Order By: Relevance
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good. Markham conducted a pre-launch and on-orbit radiometric characterization and calibration of Landsat 8 and found that the uncertainty of radiance calibration performance was within 2%, while for the reflectance calibration it was within 3% [29]. Li compared the consistency of four spectral indices for four land cover types in southeast Asia and found the correlation coefficients (R 2 ) to be a maximum of 0.96 for measurements over a two-day period [33].…”
Section: Introductionmentioning
confidence: 99%
“…The first panel, known as the "working" panel, is deployed about every eight days to characterize OLI's detectors. The second panel, known as the "pristine" panel, is deployed approximately bi-yearly to track changes in the working panel due to UV degradation from solar exposure [5].…”
Section: Landsat 8 and The Operational Land Imager (Oli)mentioning
confidence: 99%
“…The visible/near-infrared (VNIR) and panchromatic (PAN) bands (1-5 and 8) utilize silicon p-intrinsic-n (SiPIN) detectors, while the SWIR bands (6,7,9) use mercury-cadmium-telluride (HgCdTe) detectors for imaging [3]. Single and double backup detector arrays are present in each FPM for each SiPIN and HgCdTe band, respectively [4,5]. In addition to FPM-level staggering, the detectors in each FPM are staggered in even-odd sets, as shown in Figure 1b.…”
Section: Landsat 8 and The Operational Land Imager (Oli)mentioning
confidence: 99%
“…For example, recent research suggests that the integration of the Landsat-8 and Sentinel-2 data would be beneficial for applications including agricultural mapping and monitoring [5][6][7], phenological studies [8], and glacier extent mapping [9]. There are a number of pre-processing issues that need to be addressed before the well calibrated Landsat-8 [10,11] and Sentinel-2A [2,12] data can be used together or treated as effectively being sensed from the same sensor. These include handling the different sensor spectral response functions and correction for atmospheric effects [13,14], correction of surface reflectance anisotropy [15,16], and handling image tiling and geolocation differences [17][18][19].…”
Section: Introductionmentioning
confidence: 99%